From virus to diabetes therapy: Characterization of a specific insulin‐degrading enzyme inhibitor for diabetes treatment. Issue 5 (9th April 2021) - Nash, Yuval; Ganoth, Assaf; Borenstein‐Auerbach, Nofit; Levy‐Barazany, Hilit; Goldsmith, Guy; Kopelevich, Adi; Pozyuchenko, Katia; Sakhneny, Lina; Lazdon, Ekaterina; Blanga‐Kanfi, Shani; Alhadeff, Raphael; Benromano, Tali; et al.
Abstract: Inhibition of insulin‐degrading enzyme (IDE) is a possible target for treating diabetes. However, it has not yet evolved into a medical intervention, mainly because most developed inhibitors target the zinc in IDE's catalytic site, potentially causing toxicity to other essential metalloproteases. Since IDE is a cellular receptor for the varicella‐zoster virus (VZV), we constructed a VZV‐based inhibitor. We computationally characterized its interaction site with IDE showing that the peptide specifically binds inside IDE's central cavity, however, not in close proximity to the zinc ion. We confirmed the peptide's effective inhibition on IDE activity in vitro and showed its efficacy in ameliorating insulin‐related defects in types 1 and 2 diabetes mouse models. In addition, we suggest that inhibition of IDE may ameliorate the pro‐inflammatory profile of CD4 + T‐cells toward insulin. Together, we propose a potential role of a designed VZV‐derived peptide to serve as a selectively‐targeted and as an efficient diabetes therapy.